The Management Model of Sustainable Volunteer Tourism - Muharto, Muharto; Ulidam, Noho; Jauhar, Nurlaela (Management Department, Universitas Islam Negeri Alauddin Makassar, Indonesia, 2022)
This study aims to analyze volunteer tourist satisfaction and host community perceptions and design a sustainable volunteer tourism management model. This research includes qualitative research using mixed analysis methods. The data consists of primary and secondary data from Afo Tour and Travel North Maluku, Volunteer Tourists, and the host community in 2018, 2019 and 2021. The study found that volunteer tourism provides satisfaction for tourists and host communities. The most dominant factors providing satisfaction are Nature Tourism, Marine tourism and Shark feeding attractions, Knowledge transfer, Outbound and Culinary. Tourist satisfaction has an impact on loyalty to volunteer tourists. Volunteer tourism managers must implement a “two-sided satisfaction model” that emphasizes the satisfaction of tourists and host communities as the key to achieving the sustainability of volunteer tourism.